Electrical conductivity and dielectric constant of samarium phosphate glasses - Ab. Aziz, Sidek; Collier, I. T.; Hampton, R. N.; Saunders, G. A. (Taylor & Francis, 1989)
The first measurements of the d.c. electrical conductivity and the low-frequency (static) dielectric constant of samarium phosphate glasses (in the composition range 5 to 25 mol% Sm2O3) are reported. A break in the slope of the Arrhenius plot divides the conductivity data into two temperature regimes, the conductivity mechanism at low temperatures having a lower activation energy than that at higher temperatures. An increase of Sm2O3 glass modifier content results in a decrease in the absolute value of the conductivity. The data are consistent with small-polaron transport and hence small-polaron theory has been used to establish the characteristic energies of the carriers. The dielectric constants range from 5.4 for a glass containing 5mol% Sm2O3 to 8·1 for that with 2Smol% Sm2O3; the temperature dependences of the dielectric constants are linear and positive, as is usual for glasses.